The Long-Term Public Health Impact of a Community-Based Participatory Research Project for Health Promotion Among Socially Disadvantaged Women—A Case Study Protocol - Abu-Omar, Karim; Ziemainz, Heiko; Loss, Julika; Laxy, Michael; Holle, Rolf; Thiel, Ansgar; Herbert-Maul, Annika; Linder, Stephanie; Till, Maike; Sauter, Alexandra (Frontiers in Public Health, 2021)
Introduction: Community-based participatory research (CBPR) is considered to be of high potential for health promotion among socially disadvantaged groups. However, the long-term implementation and transfer of these approaches remain challenging, and the public health impact they achieve is difficult to study. This also pertains to the potential health effects and cost-effectiveness of CBPR. This study protocol describes the follow-up case study (NU-BIG) after 15 years of the BIG project (“movement as investment in health”), a project to promote physical activity among socially disadvantaged women. Through a participatory approach BIG empowers the adressed women to plan and implement low-thresholf physical activity offers. Since the project started in 2005 it was transferred to 17 communities in Germany. Materials and Analysis: NU-BIG intends to examine the long-term effects, including economic aspects, of the BIG project on individual and structural levels at all project sites as well as it’s long-term implementation and transfer. NU-BIG is a cross-sectional and longitudinal study using a mixed method approach. For the longitudinal section, we re-analyse existing data from former BIG evaluations. For cross-sectional data collection we use questionnaires and conduct qualitative interviews and focus groups. Women who take part in BIG programme offers are part of the research team and will use the photo-voice approach to report on the effects of BIG. The study population consists of about 800 women who participate in BIG project offers and 50 persons involved in the implementation of the BIG project at local sites. Discussion: The expected results from NU-BIG are highly relevant for studying the long-term public health impact of CBPR. In particular, this project intends to answer questions on how the transfer of such projects can succeed and which factors determine if a CBPR project can be sustained at the community level. Eventually these results can contribute to the further development of participatory approaches to provide effective health promotion among socially disadvantaged groups.